The impact of Ca2+ on the protective mechanisms of the photosystem under drought stress - Yanli Wei; Tongen Zhang; Tongtong Yao; Zihan Wang; Yanhui Che; Huihui Zhang (Journal of Plant Interactions)
External calcium ions (Ca2+) play a crucial role in mitigating drought stress in plants, as revealed through physiological and transcriptomic analyses using tobacco (Nicotiana tabacum L) as a model system. Under drought stress, leaves wilted, chlorophyll content decreased. The maximum photochemical efficiency of PSII (Fv/Fm) and the photosynthetic performance index decreased, fluorescence intensities at the K and L points increased, Y(NPQ) increased, net photosynthetic rate (Pn) decreased, and PSI activity (ΔI/Io) was reduced. Upon application of external calcium under drought conditions, leaf wilting was reduced, chlorophyll content increased, Fv/Fm, PIabs, and PItotal improved, fluorescence intensities at the K and L points as well as Y(NPQ) decreased, cyclic electron transport and Pn were enhanced, stomatal aperture increased, and ΔI/Io improved. Transcriptomic analysis revealed a significant reduction in the expression of genes related to the PSI and PSII reaction centers, ATP synthesis, electron transport, and antenna proteins under drought stress. The application of calcium significantly alleviated the drought-induced downregulation of these genes. In summary, Ca2+ reduces water loss in plants, increases chlorophyll content in leaves, restores PSII reaction center activity, ensures efficient photosynthetic electron transport, maintains thylakoid membrane stability, enhances cyclic electron transport, and reduces damage to the photosystem.